Split crown technique for mass propagation of pineapple (Ananas comosus L.) var. queen - Ravelo, Sarah M.; Ramos, Arsenio D. (Annals of Tropical Research, 2019)
The major problem limiting large scale commercial production and/or expansion of pineapple production is the difficulty in obtaining large quantity of quality planting materials due to slow rate of multiplication by conventional methods of propagation that mostly relies on the use of suckers and slips.. The study investigated the effect of the methods of crown preparation on the sucker production of pineapple var. Queen and to evaluate the horticultural qualities of suckers produced from plantlets prepared using different methods of crown preparation. Destroying the growing point without splitting reduced percentage survival of plantlets but destroying the meristem and splitting the crown into two or four sections improved survival comparable to the intact crown. Destruction of the growing point and then splitting the crown promoted emergence and increased the number of suckers relative to the intact crown which did not produce suckers after, 3 months from planting. Increasing the number of sections prepared per crown (from two to four) did not reduce the number of suckers produced per plantlet and thus increased the multiplication rate by 7 and 8 times, respectively. The method of crown preparation did not significantly influence the early growth performance (survival, height, number size of leaves) of the harvested & suckers during the first 6 months potting. Among the three methods of crown after preparation, destroying the meristem and splitting into two or four produced more number of ready-to-plant Queen pineapple suckers (1-ft tall) within a period of 5 months.